New Species of Charophyta, Chara polyacantha A. Braun, in Lake Engure, Latvia - Zviedre, Egita; Grinberga, Laura (Biodiversity: Research and Conservation, 2012)
The new charophyte species for Latvia, Chara polyacantha A. Braun, was described. This species was found in Lake Engure, the third largest lake of Latvia. In 2010, C.†polyacantha covered small, approximately 25 m2 patch, growing both in a monodominant stand and mixed with C. tomentosa in the central part of the lake.